What the God-seekers found in Nietzsche : the reception of Neitzche's Übermensch by the philosophers of the Russian religious renaissance - Grillaert, Nel (Studies in Slavic literature and poetics ;, 2008)
At the end of the nineteenth and the beginning of the twentieth century, a large and varied group of the Russian intelligentsia became fascinated by Friedrich Nietzsche, whose provocative ideas inspired many of them to overcome obsolete traditions and to create new values. Paradoxically, the German philosopher, who vigorously challenged the established Christian worldview, invigorated the rich ferment of religious philosophy in the Russian Silver Age: his ideas served as a fruitful source of inspiration for the philosophers of the Russian religious renaissance, the so-called God-seekers, in their quest for a new religious consciousness. Especially Nietzsche¿s anthropology of the Übermensch was instrumental in their reformulation of Christianity. This book explores how three pivotal figures in the Russian religious reception of Nietzsche, i.e. Vladimir Solov¿ëv, Dmitrii Merezhkovskii and Nikolai Berdiaev, engaged in a vacillating yet highly prolific debate with Nietzsche and how each of them appropriated his anthropology of the Übermensch in their religious philosophy. In order to explain Merezhkovskii¿s and Berdiaev¿s assessment of Nietzsche, the author highlights the significance of Dostoevskii: only by reading Nietzsche through the prism of Dostoevskii could both God-seekers pin down the religious ramifications of Nietzsche¿s thought. This book will be of interest to anyone fascinated by Nietzsche, Dostoevskii, Russian religious philosophy, Russian history of ideas and reception studies. Nel Grillaert is a Postdoctoral Research Fellow of the Research Foundation ¿ Flanders (FWO) and is affiliated with Ghent University, Belgium. She has published several articles on the Russian religious reading of Nietzsche and on religious motives in the works of Dostoevskii.